Influence Of Red Bean Flour Subtitution (Phaseolus vulgaris L.) On The Chocolate Biscuits On Customer’s Acceptance - Inasya Larasintya Jesriani; Mahdiyah Mahdiyah; Nur Riska (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This study aims to determine the Influence Of Red Bean Flour Subtitution (Phaseolus vulgaris L.) On The Chocolate Biscuits On Customer’s Acceptance, which imcludes aspect of colour, aroma, taste and texture. This research was conducted from January 2020 to March 2020 in Labotarorium Pastry and Bakery, State University of Jakarta. The research began with the manufacture of a standard formula of chocolate biscuits, then then made red bean flour. Dried red beans soaked for 24 hours until fluffy, peeled, dried and mashed. The research continued by substituting red bean flour into chocolate biscuit dough with percentages of 50%, 60% and 70%. Then this chocolate biscuit was tested with organoleptic test to 3 expert panelists (Lecturer of Food Quality Education) and consumer acceptability test to 25 rather trained penlis (Students of The Food Quality Education Study Program of Universitas Negeri Jakarta) which includes aspects of the color, taste, aroma, and texture of the chocolate biscuits The results of the analysis using the Friedman test with = 0.05 showed that the substitution of red bean flour in the manufacture of chocolate biscuits with a different percentage had no effect on consumer acceptance in terms of color, aroma, taste and texture. Based on all aspects tested, the percentage of 70% is the recommended percentage. This accpeteble to the community and to optimize the use of red bean flour in chocolate biscuit products as a functional food. According to the results of validation tests conducted on 3 expert pnelists, 70% red bean flour subtituted chocolate biscuits had a brownish maroon cocor, no red bean aroma, red bean taste and cruchy texture.